Cocaine cue‐induced mesocorticolimbic activation in cocaine users: Effects of personality traits, lifetime drug use, and acute stimulant ingestion. (31st August 2021) - D'Amour‐Horvat, Valérie; Cox, Sylvia M. L.; Dagher, Alain; Kolivakis, Theodore; Jaworska, Natalia; Leyton, Marco
Abstract: Stimulant drug‐paired cues can acquire the ability to activate mesocorticolimbic pathways and lead to new bouts of drug use. Studies in laboratory animals suggest that these effects are augmented by progressively greater drug use histories, impulsive personality traits, and acute drug ingestion. As a preliminary test of these hypotheses in humans, we exposed cocaine users ( n  = 14) and healthy volunteers ( n  = 10) to cocaine‐related videos during two functional magnetic resonance imaging (fMRI) sessions, once following acute administration of placebo and once following d ‐amphetamine (0.3 mg/kg, p.o.). Across sessions, cocaine users showed larger cocaine cue‐induced responses than healthy controls in the associative striatum and midbrain. Among the cocaine users, larger drug cue‐induced responses during the placebo session were correlated with higher Barratt Impulsiveness Scale (BIS‐11) nonplanning scores (associative striatum) and greater lifetime use of stimulant drugs (limbic, associative, and sensorimotor striatum). The administration of d ‐amphetamine did not augment the cue‐induced activations, but, in cocaine users, drug cue‐induced striatal activations were more widespread following prolonged cocaine cue exposure. Together, these effects of past and present drug use might aggravate the risk for stimulant drug use problems. Abstract : Cocaine users and healthy volunteers underwent a cocaine cue exposure paradigm while undergoing functional magnetic resonance imaging (fMRI) scanning, once following the administration of a placebo and once following d‐amphetamine. Striatal responses were larger in cocaine users than healthy controls and largest in those with the greatest lifetime histories of stimulant drug use. Among the cocaine users, cocaine cues engaged the limbic and associative striatum on the placebo session and sensorimotor striatum on the d‐amphetamine session.